Clinical Profile and Outcome of Myocarditis in Children at Dr. Hasan Sadikin General Hospital Bandung from 2008 to 2012 - Nurtriandari, Erza; Budi, Rahmat; Soeherman, R. B. (Althea Medical Journal, 2017)
Background: Diagnosis of myocarditis in children is still challenging due to its inconsistent and wide spectrum of clinical manifestations. There is no specific laboratory test available. This may obscure the true incidence of myocarditis. The purpose of this study was to describe clinical profile and outcome of myocarditis in children.Methods: A descriptive study was performed using 80 medical records of hospitalized pediatrics patients with myocarditis in Dr. Hasan Sadikin General Hospital Bandung from January 2008 to December 2012. The obtained data were age, gender, nutritional status, etiology, chief complaint, physical examination, laboratory findings, other examinations and outcome of the disease. The collected data were analyzed and presented in the form of frequency distribution.Results: The mean age of the patients was 91.46 (45.93) months old, predominantly male. The most etiology was dengue infections (61%). High fever was found as the most common chief complaint (38%) and the most common found in physical examinations were tachypnea (65%) and hepatomegaly (55%). Electrocardiography (ECG) showed the first degree atrioventricular block (AV block) (35%), aspartate aminotransferase (AST) and creatine kinase myocardial band (CKMB) was increased in more than 80% of patients. The majority of patient was improved. Shock was the common complication.Conclusions: Dengue is the most etiology of myocarditis etiology. Tachypnea, hepatomegaly, the first degree AV block in ECG, elevated AST and CKMB were the most common presentations. Most of the patients were improved during treatment. [AMJ.2017;4(1):118â24DOI:Â 10.15850/amj.v4n1.1031Â